A model bridging team brand experience and sponsorship brand experience. Issue 4 (6th November 2017) - Biscaia, Rui; Trail, Galen; Ross, Stephen; Yoshida, Masayuki
Abstract : Purpose: Previous research has focused on the antecedents of fan loyalty or the link between fans and the team on sponsorship reactions, but no comprehensive framework has been developed to combine these perspectives. The purpose of this paper is to present an integrated framework of how team brand experience during the season impacts sponsorship brand experience. Design/methodology/approach: To create the conceptual model, a comprehensive search of peer-reviewed articles was conducted in electronic databases and journal reference lists. The authors identified constructs from prior research aimed at understanding sponsorship effectiveness. These constructs not only included aspects of the sponsorship brand experience, but also aspects within the team brand experience that form the link between consumers' responses derived from team-related stimuli and the responses evoked by sponsor-related stimuli. Findings: This conceptual framework yields a set of 11 propositions regarding fans' interactions with both team and sponsorship brands highlighting how to strengthen the bond between fans, teams, and sponsors. It provides a comprehensive understanding of this phenomenon and identifies opportunities to increase fan support and the appeal of professional teams to potential sponsors. Originality/value: This study extends previous research by providing a unique conceptual framework that highlights the importance of understanding how fans view both the team brand and the sponsor brand. Several suggestions for future studies and strategies to increase the benefits for both teams and sponsors can be drawn from this framework.